Piet Mondrian’s Intuitive Neo-Plastic Art and Zen Notion of Mu-shin - Fallahzadeh, Ali; Yousof, Ghulam Sarwar (University of Malaya Cultural Centre, 2016)
Reviewing scholarly materials pertinent to prominent Dutch painter Piet Mondrian (1872-1944), one faces perplex interpretations of his essays based on Western thought such as Hegelism, Platonism, Neo-Platonism, and Theosophy. This research strives to shed a novel light on Mondrian’s esoteric essays in respect to the pivotal notion of “pure intuition” in Neo-Plastic art from antirational standpoint of Zen Buddhism. To this end, the concepts of “inferior intellect” and “pure intuition”, discussed in Mondrian’s essays, are confronted with an antirational approach of Zen in disclosure of truth. Moreover this paper chronologically depicts the kinships between the pivotal Zen concept of mu-shin (no-mind) and Mondrian’s notion of pure intuition as a universal vision which is further exemplified through three Neo-Plastic artworks representing three phases of Mondrian’s artistic career. The results of this paper illuminate Mondrian’s quasi-philosophical essays within the role of “pure intuition” through the ideology of Zen Buddhism.